Interior Galeri Kebaya Indonesia di Surabaya - Cheung Vivi Chandra (Intra, 2014)
Interior Design Indonesian Gallery of Kebaya in Surabaya , it’s purpose is to facilitate the public. The gallery where there is a museum that promotes the historical value of kebaya from time to time. It also provides public area likes, restaurant / café, to enhance the comfort of visitors. This gallery itself was designed theme with the concept called “Complexity” which is describe the difficulty and the beauty of kebaya and re-live in this modern era. Spiral has been modified more simple become circle form., and apllied in layout, furniture, even elements in interior.